북한 REDD+ 사업 참여를 위한 4대 요건 역량 평가 분석 - 박소영; So-young Park; 김은희; Eun Hee Kim (한국산림과학회지, 2025)
파리협정이 채택된 이후 남북은 기후위기대응을 위한 국제질서에 동참하고 있다. 북한도 국가온실가스 감축목표를 발표하고, 온실가스 적응과 감축 수단 중 하나로 황폐 산림복구를 약속하였다. 국제적으로 탄소흡수원인 산림의 역할과 REDD+사업이 대두되면서 북한의 참여 가능성이 높아지고 있어, 사업참여를 위한 4대 요건을 평가하였다. ‘국가전략과 행동계획수립’ 과 ‘국가산림모니터링’은 일부 충족된 것으로 판단된다. 온실가스 MRV 보고를 위한 ‘산림배출기준선/ 산림기준선 설정’은 과학기술이 뒷받침되어야 하기 때문에 현재 불충분하며 향후 외부 지원이 필요하다고 판단하였다. 안전장치7종 중 가장 부족한 부분은 이행결과 역전 및 배출 지역 이전 방지 관련 사항이었다. 그러나 이 경우 북한이 REDD+ 사업을 진행하면서 충분히 보강할 수 있을 것이다. Since the adoption of the Paris Agreement in 2015, South and North Korea have participated in the international order for climate crisis. In particular, North Korea announced its Intended Nationally Determined Contributions for 2016 and highlighted forest restoration as a key strategy for mitigating and reducing greenhouse gas. Given the role of forests as carbon sinks, and the increased scholarly attention attracted by Reducing Emissions from Deforestation and Forest Degradation+ (REDD+) projects internationally, the likelihood of North Korea’s participation is also increasing. This study aims to evaluate the four key elements of participation in REDD+ projects. National strategy or action plan and national forest monitoring system were deemed partially fulfilled. However, greenhouse gas MRV (Measure, Report, and Verify) reporting of forest reference (emission) levels was insufficient due to the need for scientific and technological support, which requires external assistance. Among the seven domains of the Safeguard Information System, the most lacking aspect pertained to addressing the risk of reversals and decreasing the displacement of emission. Nevertheless, North Korea is capable of sufficiently addressing these issues as it progresses with REDD+ projects.